A Review of Resistance to Polymyxins and Evolving Mobile Colistin Resistance Gene (mcr) among Pathogens of Clinical Significance - Shakeel Shahzad; Mark D. P. Willcox; Binod Rayamajhee (MDPI AG, 2023)
The global rise in antibiotic resistance in bacteria poses a major challenge in treating infectious diseases. Polymyxins (e.g., polymyxin B and colistin) are last-resort antibiotics against resistant Gram-negative bacteria, but the effectiveness of polymyxins is decreasing due to widespread resistance among clinical isolates. The aim of this literature review was to decipher the evolving mechanisms of resistance to polymyxins among pathogens of clinical significance. We deciphered the molecular determinants of polymyxin resistance, including distinct intrinsic molecular pathways of resistance as well as evolutionary characteristics of mobile colistin resistance. Among clinical isolates, Acinetobacter stains represent a diversified evolution of resistance, with distinct molecular mechanisms of intrinsic resistance including naxD, lpxACD, and stkR gene deletion. On the other hand, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa are usually resistant via the PhoP-PhoQ and PmrA-PmrB pathways. Molecular evolutionary analysis of mcr genes was undertaken to show relative relatedness across the ten main lineages. Understanding the molecular determinants of resistance to polymyxins may help develop suitable and effective methods for detecting polymyxin resistance determinants and the development of novel antimicrobial molecules.